Devkota’s Realization of Ultimate Reality: A Vedantic Reading on "Shūnyamā Shūnyasarī" - Bhatta, Damaru Chandra (The Outlook: Journal of English Studies, 2022)
This article analyzes Laxmi Prasad Devkota's Nepali poem "Shūnyamā Shūnyasarī" ("Being Empty in Emptiness") by using the insights of the Vedanta that has a special focus on non-dual (Advaita) philosophy. The poem is devotional as well as confessional, which is a common theme of South Asian literature composed in the Bhakti ("devotional”) tradition. Devkota, the last hour of his life, realized that he really went astray and could not follow his own tradition, culture, religion and spirituality properly. Although it was too late for him to correct his past mistakes, he accepted Lord Shrī Krishṇa as the essence of life; all the other things are Sūnya (“void, Māyā, illusion, nothing, or meaningless"). Sūnya means asat ("unreal"), which is not in existence really. Finally, the poet Devkota acknowledged that he vanished into void like a void being meaningless. He could not devote his life to seek Lord Shrī Krishṇa, who is the ultimate reality or essence of the universe. Devkota suggests that the goal of life should be to attain the ultimate reality for eternal liberation or perpetual peace and unbound joy. Life should be spent for this spiritual purpose. Life becomes meaningless if one dies without this kind of spiritual awareness.